اقبال کی انگریزی نثر میں قرآنی آیات کے تراجم ( تحقیقی و تنقیدی جائزہ): TRANSLATION OF THE QURANIC VERSES IN IQBAL’S ENGLISH PROSE: A CRITICAL STUDY (Zia e Tahqeeq, 2025)
Several collections of English and Urdu prose of Allama Iqbal have been edited and printed since 1930. Their deep study shows that these collections have not been edited and annotated carefully. Even verses of the Holy Quran, their English and Urdu translation and references are not quoted with full accuracy. These collections need editing and correction. It is dire need of time to edit and print standard copies of Iqbal’s English and Urdu prose under the titles: Kuliyat-e-Iqbal (English Prose) and Kuliyat-e-Iqbal (Urdu Prose). The present study is an attempt to evaluate the accuracy of translation of the Quran in English papers of Iqbal.